A la búsqueda de los tiempos perdidos. Estado de los archivos locales: el caso de Hidalgo - Bautista, Mariano E. Torres; Centro de Investigaciones y Estudios Superiores en Antropología Social-Distrito Federal, México (2014)
This paper presents an over view of the largest repositories of written histor y in the state of Hidalgo. It repor ts the author’s findings and obser vations, gathered throughout archives in Pachuca and the rest of the state, which show the main flaws detected in the way most of these archives operate, particularly outside the state’s capital, and the problems generated during their use. The author’s diagnosis detects cer tain questions per taining to the formation and existence of public archives, which require urgent attention because these elements place them in risk situations.